1 x 125 mw coal fired steam power plant economic analysis at pt krakatau daya listrik - Anggraeni, Dian; Murtaqi, Isrochmani (The Indonesian Journal of Business Administration, 2018)
Abstract. This study aims to perform an economic feasibility analysis of the construction project of Coal Fired Steam Power Plant with 125 MW capacities to be performed by PT Krakatau Daya Listrik, a subsidiary company from PT Krakatau Steel This research will analyze whether an investment on the construction of Coal Fired Steam Power Plant with 125 MW capacity is financially feasible. The analysis is conducted by using Capital budgeting method through Discounted Cash Flow approach. Indicators measured are Net Present Value, Internal Rate of Return, Payback Period. In this approach also carried out the project sensitivity analysis. The construction project of a 1 x 125 MW Coal Fired Steam Power Plant is financially feasible by comparing financial feasibility parameters such as Net Present Value (NPV)> 0, Internal Rate of Return (IRR)> Cost of Capital and Payback Period less than maximum payback period that can be accepted. Based on the results of the analysis of these parameters, the construction project of Coal Fired Steam Power Plant 1 x 125 MW is feasible to be done financially with NPV value of MIDR 2,345,451, IRR 13.76% larger than WACC of 8.07% and Payback Period for 6 years 3 months. In relation to the results of financial analysis, the sensitivity analysis is used to determine the feasibility characteristics of the project on changes in investment value caused by the influence of economic variables and technical parameters. To conduct a deeper analysis, it is necessary to calculate the investment indicators by making changes (sensitivity analysis) to the key parameters that influence: EPC cost, coal price, loan interest rate, change in exchange rate and electricity tariff.Keywords: Capital Budgeting, Net Present Value, Internal Rate of Return, Payback Period, Sensitivity Analysis.